REDUKSI ION KALSIUM DALAM AIR TANAH MENGGUNAKAN ADSORBEN DARI KULIT PISANG KEPOK (Musa normalis L.) - Rismawaty Sikanna (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2016)
ABSTRACT It had been done a research with the aim to investigate the reduction of calcium ion in the soil water using adsorbents from Kepok banana (Musa Normalis L.) peel. This research used activated adsorbents with H2SO4 3 M and unactivated, with the various time of mixed until 10, 20, 30, 40, 50 and 60 minutes. The results showed that the reduction % of calcium ion of unactivated adsorbents were 2.65; 3.03; 3.79; 4.17; 4.54; 6.44; and activated were 15.15; 16.67; 19.32; 21.59; 22.73 and 23.48 respectively. Keywords: Reduction of calcium ion, soil water, Kepok banana peel.